International emission regulation in sea transport: Economic feasibility and impact. (June 2016) - Sys, Christa; Vanelslander, Thierry; Adriaenssens, Mathias; Van Rillaer, Ive
Highlights: The petrochemical lobby much more than the green lobby is the driver behind emission caps at sea. The shift from Southern-European to Northern-European ports as a consequence of emission zones at sea will be rather limited. The main liner companies seem well prepared to deal with the upcoming emission zones in their current strategies. MARPOL enforcement is to be improved. Abstract: Emissions from shipping due to the burning of the sulphur content of marine fuels conduce to air pollution in the form of sulphur dioxide and particulate matter. Various international organisations and institutions impose environmental standards on their member states to limit the emission of greenhouse gases. This paper examines both the potential effects of the emerging international maritime emission regulations on the competition between seaports and the potential underlying economic motivations fostering the discussion of introducing Emission Control Areas. It focuses on deepsea shipping. Another novelty is that the environmental issues are addressed from a policy, an economic and a legislative viewpoint. For the policy-related part, it is found that the political theory of public choice suggests that not the green lobby but rather the petrochemical lobby is the major driving factor behind the very strict emission caps. A potential port shift from Northern Europe to Mediterranean ports seems unlikely due to logistics disadvantages and service problems in Southern European ports. Finally, no convincing proof was found that the main liner companies would be unprepared for this legislation and should be persuaded to change their routes in favour of Mediterranean ports solely on account of the various emission regulations. The legal analysis, however, showed that the current enforcement regime of MARPOL Annex VI should be improved in order to rule out the possibility of a low degree of compliance and to protect the competiveness of complying ships.